Effect of histamine on the induction of differentiation/apoptosis by MRP4/ABCC4 inhibitors in AML cells: ceefourin-1 evaluation - Sahores, Ana (2021)
We previously described that both the cAMP transporter MRP4 and the histamine H2 receptor are molecular targets for Acute Myeloid Leukemia (AML) differentiation therapy. Increased intracellular cAMP concentrations play an important role in leukemic cell maturation, proliferation, and apoptosis. s. In the present study we analyzed the ability of histamine (HIST), in combination with MRP inhibitors, to induce AML cell differentiation/apoptosis, and made special focus in ceefourin-1.